A virus disease of oats in Finland similar to oat sterile-dwarf disease - Ikäheimo, Katri (Agricultural and Food Science, 1961)
The leafhopper Calligypona pellucida F. transmits a virus that causes dark green colouration, dwarfing and excessive formation of side-shoots in oats. This disease is similar to oat sterile-dwarf but differs from wheat striate mosaic. The incubation time of oat sterile-dwarf virus in the vector varied from 7 to 37 days. This virus and the wheat striate mosaic virus can infect the same plant simultaneously and seem to overwinter in their leafhopper vector. It seems likely, that oat sterile dwarf became epidemic and caused great losses in yields of oats during some years of 1950 in western Finland.